An aide memoire for a balancing act? Critiquing the ‘balance sheet’ approach to best interests decision-making - Kong, C; Coggon, J; Dunn, M; Keene, AR (Oxford University Press, 2020)
The balance sheet is commonly used as a deliberative approach to decide best interests in Court of Protection cases in England and Wales, since Thorpe LJ in Re A (Male Sterilisation) described the balance sheet as a tool to enable judges and best interests decision-makers to quantify, compare, and calculate the different options at play. Recent judgments have critically reflected on the substance and practical function of the balance sheet approach, highlighting the practical stakes of its implicit conceptual assumptions and normative commitments. Using parallel debates in proportionality, we show that the balance sheet imports problematic assumptions of commensurability and aggregation, which can both overdetermine the outcome of best interests decisions and obfuscate the actual process of judicial deliberation. This means that the decision-making of judges and best interests assessors more generally could fail to properly reflect the nature of values at stake, as well as the skills of practical judgment needed to compare such values with sensitivity and nuance. The article argues that critical reflection of the balance sheet makes vital space for a more contextualised, substantive mode of deliberation which emphasises skills of qualitative evaluation towards enhancing conditions of articulation around the range of values involved in best interests decision-making.